Analisis Kesulitan Peserta Didik dalam Menyelesaikan Soal Cerita Operasi Hitung Penjumlahan dan Pengurangan - Rozinita, Azizah; Mushafanah, Qoriati; Nugroho, Aryo Andri (Lembaga Yasin AlSys, 2023)
The purpose of this study is to characterize the sorts of errors that occur when solving math narrative problems, as well as the factors that contribute to such errors. Understanding the problem, preparing the solution, carrying out a solution plan, and re-examining are the four stages of completing narrative problems based on the polya step. The subjects of this study were third-grade children from SD N Karang Rejo 02. This study uses a qualitative method and is a form of descriptive study. The interview and observation methods were employed as research methods. The findings of the study revealed that third-grade students at SD N Karang Rejo 02 made four types of errors when solving math story problems: 1. The majority of pupils were able to understand the questions at this point, although there were a few kids who struggled. 2. Most students have been unable to create their plans at the planning stage due to a lack of knowledge, accuracy, and concentration. 3. Because the preceding phases were not carried out precisely, most students are unable to implement the plan at this point. 4. The majority of pupils do not reach the re-examination stage since they did not complete the prior level.